ПРОФЕССИОНАЛ ТӘЛИМНИҢ АБЗАЛЛЫҚЛАРЫ ҲӘМ ЭКОНОМИКАЛЫҚ ТӘРЕПЛЕРИ - Қанглибеков, Қ.Д. (ILIM hám JÁMIYET, 2020)
The article provides an overview of the benefits of vocational education. The importance of professional education in the life of a specialist is closely related to his interests and abilities. It was noted that the problem of unemployment in our society is the result of a lack of cooperation between the employer and institutions of secondary specialized education.